Digital innovations: Implications for African agribusinesses - Arthur, Kingsley Kofi; Bannor, Richard Kwasi; Masih, Jolly; Oppong-Kyeremeh, Helena; Appiahene, Peter (Smart agricultural technology, 2024)
Despite the agribusiness industry's potential, it is still characterised by a high level of conventional means of production, denying it numerous opportunities along the value chain in Africa. Meanwhile, adopting modern means of production using digital innovations can boost farmers' efficiency. Given the relevance of digital innovations within the agribusiness industry, the current paper gives an overview of digital innovations in the agribusiness industry, particularly in Africa, by synthesising existing literature on digital innovations to consolidate scattered ideas and give recommendations for practice and future studies. The PRISMA technique was adopted to synthesise 47 existing relevant articles from the Scopus database. Bibliometric tools such as VOSviewer and R-Package-Bibliometrix were used to analyse the data. From the results, most papers on African digital innovations emanated from a journal with a broader scope—Sustainability Journal (Switzerland). Most of the funding for digital innovation studies in agribusiness was sponsored by foreign donors outside the African Continent, with the Consortium of International Agricultural Research Centers in France sponsoring the most research. Based on the publication synthesis and the trend of publications, five themes, namely, digital innovations in the agricultural value chain, training and skills development through digital innovations, digital finance innovations in agribusiness, precision digital innovations: agribusiness survival, and drivers of digital innovation adoption in agribusiness were identified. From the results, digital agribusiness innovations in marketing, production, and finance have been profound in Africa, though they are skewed towards a few South, West, and North African countries. Meanwhile, the drivers and challenges of digital innovations in Africa have been mainly social, economic, political, and institutional factors. Given the results, it is recommended that, since most of the studies were primarily sponsored by foreign governments, thus betraying the commitment of the African continent's readiness to transform the agribusiness sector via innovation and technology, African Governments, first, and second, non-governmental organisations and other agricultural donors should prioritise the digitalisation of the agriculture sector by integrating them into economic development plans and making relevant resources available to all actors from upstream to downstream.